PENGEMBANGAN POTENSI BISNIS JASTIP UNTUK EKONOMI MANDIRI KARANG TARUNA DESA BABAT, LAMONGAN - Nyoman Sri Widari; Desrina Yusi Irawati; Lusi Mei Cahya Wulandari; Yohanes Okta Dwi Prastyo (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
One of the primary goals of the youth organization (Karang Taruna) is to foster an entrepreneurial spirit and promote independence as part of efforts to improve social welfare. Some members of the Babat youth organization proposed a business idea: a personal shopping service (Jastip). However, there are several areas for improvement in their current jastip business model, including limiting their products to specific categories (such as cosmetics or skincare), operating only during major events or bazaars, lacking effective business management, and not utilizing social media for promotion. The identified improvement priorities include providing training on service management and online promotion strategies, creating and actively managing social media accounts, and diversifying the range of products offered. Each activity is closely monitored and evaluated based on pre-determined performance indicators. The outcomes of this community service project include the establishment of an Instagram account for the jastip business, clear delegation of responsibilities among members, the creation of structured schedules for shopping and promotion, and the addition of new product categories to their inventory. The community service activities were successfully implemented and received enthusiastic participation from all members.